Surveillance of SARS-CoV-2 variants in Henan, China from 2023 to 2024 - Yun Song; Bicong Wu; Hongxia Ma; Yafei Li; Su Yan; Jingjing Pan; Haifeng Wang; Ying Ye; Xueyong Huang; Wanshen Guo (Frontiers in Cellular and Infection Microbiology)
ObjectiveIn January 2023, China implemented the “Class B Management” policy, marking a new phase in COVID-19 control. As new SARS-CoV-2 variants continue to emerge, some have shown significant immune evasion, posing challenges to epidemic control efforts. To manage the pandemic effectively, Henan Province launched a surveillance program for SARS-CoV-2 variants, systematically analyzing their clinical characteristics and epidemiological patterns.MethodsThis study collected genomic sequence data from 5,965 COVID-19 cases between January 1, 2023, and March 17, 2024, using the Henan Province SARS-CoV-2 variant surveillance system. Genome sequence analysis was performed with CLC Genomics Workbench, and genotyping and sequence alignment were carried out using the Nextclade platform. The clinical severity of different variants was assessed in relation to patient sex, age, clinical classification, and vaccination status.ResultsBetween Week 1 of 2023 and Week 11 of 2024, a total of 5,965 complete SARS-CoV-2 genome sequences were obtained, including 3,004 male (50.36%) and 2,961 female (49.64%) cases. The majority of cases were mild (5,451 cases, 91.38%), followed by moderate (311 cases, 5.21%) and severe or critical cases (203 cases, 3.4%). The predominant variants included BA.5.2, XBB, and BA.2.86. BA.5.2 was dominant until April 2023, after which it was gradually replaced by XBB. From December 2023, BA.2.86 began to increase and became the predominant variant by January 2024. The XBB variant exhibited a significantly lower rate of severe cases, with most infections being mild (P < 0.05). Male patients, the elderly, and certain variants (e.g., BA.5.2) were associated with more severe outcomes, while XBB and BA.2.86 showed lower pathogenicity, with a marked reduction in severe and fatal cases (P < 0.05).ConclusionAs SARS-CoV-2 variants evolve, the incidence of severe cases has progressively decreased. Both XBB and BA.2.86 variants exhibit lower pathogenicity. This study provides vital scientific evidence on the epidemiological features, clinical manifestations, and control strategies of SARS-CoV-2 variants. It underscores the importance of continuous viral surveillance and genomic sequencing to guide public health decision-making.